PENGARUH TERPAAN MEDIA SOSIAL INSTAGRAM MENGENAI PRODUK BOIKOT DAN KONFLIK PALESTINA – ISRAEL TERHADAP KEPUTUSAN PEMBELIAN PRODUK BOIKOT - Nur Hasanah, Anisa; Luqman, Yanuar; Dwiningtyas Sulistyani, Hapsari (Interaksi Online, 2024)
The conflict between Palestine and Israel has been ongoing for a long time and flared up again in October 2023. This conflict has been widely discussed on social media, including Instagram. The escalation in 2023 led to a resurgence of the BDS (Boycott, Divestment, Sanctions) movement as a response to policies and practices deemed to violate human rights and international law. One consequence of the Palestine-Israel conflict is that the public has increasingly voiced support for boycotts through Instagram, resulting in decreased sales for companies affiliated with Israel. This study aims to examine whether there is an influence of Instagram social media exposure regarding boycott products and the Palestine-Israel conflict on the decision to purchase boycott products. This research is an explanatory type of study using a non-probability sampling technique involving 100 respondents. The theory used is the Cognitive Response Theory and the Cognitive Response Model as a foundation to understand the influence of Instagram social media exposure regarding boycott products and the Palestine-Israel conflict on the decision to purchase boycott products. The research utilizes multiple regression analysis techniques, based on hypothesis testing of the exposure to boycott products and the Palestine-Israel conflict on the decision to purchase boycott products, which yielded 0.007 > 0.05. Simultaneously, both independent variables (X) do not have an influence on the dependent variable (Y), thus the hypothesis is rejected. Furthermore, the R square result in the study is 9.6%, indicating a small effect. The results of this study are not significant due to other factors influencing the independent variables that were not included in the research, and the theory used is not sufficient to thoroughly explain the research results.